1974
DOI: 10.1073/pnas.71.2.359
|View full text |Cite
|
Sign up to set email alerts
|

Differential Interaction of Cholesterol with Phosphatidylcholine on the Inner and Outer Surfaces of Lipid Bilayer Vesicles

Abstract: The Proton nuclear magnetic resonance (PMR) spectroscopy has been applied extensively in recent years to elucidate the structural or conformational properties of phospholipids and biomembranes (1). Most of these studies, however, are concerned primarily with the mobility of fatty acyl chains of the bilayer (2, 3). As reported several times (4-6), paramagnetic ions such as europium (Eug+) added to the exterior of lipid vesicles shift the field position of the -N+(CHI3)3protons of phosphatidylcholine (PC) molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
30
0

Year Published

1976
1976
1990
1990

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(39 citation statements)
references
References 17 publications
9
30
0
Order By: Relevance
“…The results of this analysis, tabulated in Table 11, show an approximate two-fold preference of cholesterol and PE for the inside surface and an approximate four-fold preference of PA-for the inside surface. The cholesterol result is in agreement with the results of Huang et al (1974) who have given evidence that egg PC bilayer membranes with overall mole fractions of cholesterol above 30 ~ have a larger mole fraction of cholesterol on the inner half of the bilayer. These workers interpreted the preference as the result of replacement of PC molecules with unsaturated chains by cholesterol on the inner layer.…”
Section: Inside Vs Outside Distribution In Mixed Lipid Systemssupporting
confidence: 92%
See 1 more Smart Citation
“…The results of this analysis, tabulated in Table 11, show an approximate two-fold preference of cholesterol and PE for the inside surface and an approximate four-fold preference of PA-for the inside surface. The cholesterol result is in agreement with the results of Huang et al (1974) who have given evidence that egg PC bilayer membranes with overall mole fractions of cholesterol above 30 ~ have a larger mole fraction of cholesterol on the inner half of the bilayer. These workers interpreted the preference as the result of replacement of PC molecules with unsaturated chains by cholesterol on the inner layer.…”
Section: Inside Vs Outside Distribution In Mixed Lipid Systemssupporting
confidence: 92%
“…Michaelson, Horwitz and Klein, (1973) have used nuclear magnetic resonance techniques to show that phosphatidyl glycerol (PG) concentrates on the inside surface of vesicles prepared from PG-PC mixtures. Huang et al (1974) have studied vesicles prepared from cholesterol-PC mixtures with a variety of physical techniques and have concluded that cholesterol distributes preferentially on the inside surface. Litman (1973) has used data on the inside-outside distribution of PE in vesicles made from PE/PC mixtures and has made calculations using estimates of the vesicle size to demonstrate a tendency for PE to be concentrated on the inside surface.…”
Section: Inside Vs Outside Distribution In Mixed Lipid Systemsmentioning
confidence: 99%
“…Thus above 20-30moles cholesterol/100moles, the cholesterol composition of the outer monolayer of the vesicle remains essentially constant, with all additional cholesterol being incorporated in the inner monolayer. These conclusions are fully supported by NMR measurements of the outside-inside distribution of phospholipid molecules across the bilayer of unsaturated phosphatidylcholine vesicles containing cholesterol (Huang et al, 1974;de Kruijff, Cullis & Radda, 1975, 1976. This asymmetric packing of cholesterol means that the number of phosphatidylcholine molecules per vesicle must also increase with increasing cholesterol composition, in order not to have an unrealistically high cholesterol/phospholipid ratio in the inner monolayer.…”
Section: Discussionmentioning
confidence: 63%
“…Conversely, the asymmetric packing effect could give rise to the triggering of rapid transbilayer migration of cholesterol by changes in lateral segregation. This might be one possible mechanism by which regions of high radius of curvature could be centers of high biological activity, as suggested by Huang et al (1974).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation